The relationship between labor market concentration and wages in Mexico - Oseguera Sauri, Ana Cristina (Estudios Económicos de El Colegio de México, 2022)
This paper presents a panel data estimation of the relationship between labor marker concentration and wages. Labor market concentration is measured using the Herfindahl-Hirschman Index (HHI) of employment. In the formal sector, results show that an increase of one standard deviation (3,566 points) of the HHI is associated with an increase in wages of between 2.1% and 2.9%. This elasticity depends on labor productivity. In the informal sector, results show that an increase of one standard deviation (3,242 points) of the HHI is associated with an increase in wages of between 4.5% and 6%. This elasticity depends on capital intensity.